2011
DOI: 10.1038/nrneurol.2011.60
|View full text |Cite
|
Sign up to set email alerts
|

Depression and risk of developing dementia

Abstract: Depression is highly common throughout the life course and dementia is common in late life. The literature suggests an association between depression and dementia, and growing evidence implies that timing of depression may be important to defining the nature of the association. In particular, earlier-life depression or depressive symptoms consistently have been shown to be associated with a 2-fold or greater increase in risk of dementia. In contrast, studies of late-life depression have been more conflicting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
809
4
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 962 publications
(866 citation statements)
references
References 124 publications
34
809
4
19
Order By: Relevance
“…Further, the association between depression and AD/dementia may be dependent on the age when depression was diagnosed, or severity or episodic nature of the disease (3,6), but this was beyond the scope of our study.…”
Section: Limitationsmentioning
confidence: 88%
See 2 more Smart Citations
“…Further, the association between depression and AD/dementia may be dependent on the age when depression was diagnosed, or severity or episodic nature of the disease (3,6), but this was beyond the scope of our study.…”
Section: Limitationsmentioning
confidence: 88%
“…Most of the previous studies have assessed the association between depression and AD, with inconsistent findings (6). A meta-analysis (7) concluded that depression is a risk factor rather than a prodromal symptom of AD as the width of time window between exposure and outcome was positively related to the risk of developing AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 These hypotheses are not mutually exclusive and data exists to support aspects of all three. Moreover, all three hypotheses are consistent with a neural network model of depression described above, as well as the idea of multi-process biological vulnerability, which we will elaborate on later in this article.…”
Section: Current Hypotheses For Biological Mechanisms Promoting Lldmentioning
confidence: 99%
“…The dementia prodrome hypothesis 30 is based on the observation that older adults with depressive symptoms have a much greater risk of developing dementia upon follow-up compared to those without depressive symptoms. 44-45 Multiple, non-mutually exclusive etiological causes have been proposed to explain this association between depression and dementia 46 and, generally, they all propose that the processes that play an etiological role in disrupting the neural circuitry underlying cognitive function and thus lead to dementia, also disrupt the neural network underlying mood.…”
Section: Current Hypotheses For Biological Mechanisms Promoting Lldmentioning
confidence: 99%